Affective Reconfiguration and Lateral Memories: Antipatriarchal Men’s Activisms in Chile; RECONFIGURACIÓN AFECTIVA Y MEMORIAS LATERALES: ACTIVISMOS MASCULINOS ANTIPATRIARCALES EN CHILE - Jeanneret-Brith, F (Universitat Autonoma de Barcelona, 2026)
In this article we delve into antipatriarchal men’s collectives in Chile from a qualitative research on gender disputes and social memories. From their narratives, we show how these masculine activisms distance themselves from the logic of redemption and from militant legacies, proposing fragile and huacho bonds, without lineage or promise. In these modes of being-together we trace how the affective embodiment of gender is reconfigured in activism and, in turn, how this is linked to social memories that are lateral to the dominant narratives about the dictatorship. © (2026), (Universitat Autonoma de Barcelona). All right reserved.